DAKWAH JURNALIS TRIBUN JABAR: STUDI KOMUNIKASI PROFETIK - Rano Hardiana Diansah; Wawan Setiawan (An-Nahdliyyah: Jurnal Studi Keislaman, 2023)
The characteristics of the Prophet and Apostle include shiddiq (true), amanah (trustworthy), tabligh (adjusting according to facts), and fathanah (according to the rules of the press or journalistic code of ethics). These four characteristics are part of prophetic communication that needs to be implemented by a journalist. This is necessary for a reporter or journalist in journalistic activities to have a reference for making reports that are correct, reliable, based on facts, and in accordance with the journalistic code of ethics. The research method used is a qualitative method with a case study approach. By conducting observations and in-depth interviews with research subjects determined purposively. Research with a qualitative approach uses phenomenological methods and interpretative paradigms. This paradigm sees the truth of social reality as having different results, depending on the social actors. Through the constructivism paradigm, researchers want to know how subjects perceive a phenomenon of prophetic journalism in their daily lives so that it can be interpreted and explained by research subjects according to their understanding of their respective applications. This research shows that the West Java Tribune has implemented prophetic journalism in producing news, although not yet comprehensively, but at least journalists at the West Java Tribune have implemented the 4 morals of the Prophet and Apostle in their journalistic activities in the field. The implementation of Siddiq's morals in journalistic activities at the West Java Tribune is that there "adheres to journalistic ethics and one of them is how to be precise, accurate and trustworthy. Implementation of morals of trust in journalistic activities at the West Java Tribune "One of the points in journalistic ethics is that we must convey valid information, information that can truly be confirmed. Implementation of tabligh morals in journalistic activities at the West Java Tribune "the news we convey is always based on facts and data available in the field, for example, there was an accident involving one or two motorbikes, so that is conveyed according to the facts in the field and the implementation of fathanah morals in journalistic activities in West Java Tribune "So in the process of making news we cannot make news that is not based on existing facts, neither exaggerated nor reduced. The process of making news also has a role for journalists.